Incorporating Electrochemical Halide Oxidation into Drift‐Diffusion Models to Explain Performance Losses in Perovskite Solar Cells under Prolonged Reverse Bias. Issue 10 (20th January 2021) - Bertoluzzi, Luca; Patel, Jay B.; Bush, Kevin A.; Boyd, Caleb C.; Kerner, Ross A.; O'Regan, Brian C.; McGehee, Michael D.
Abstract: Partial shading of a solar module can induce a set of cells within the module to operate under reverse bias. Studies have shown that metal halide perovskite solar cells with a wide variety of compositions and contacts exhibit interesting behavior in reverse bias that includes both reversible performance loss and non‐reversible degradation. In this paper, an advanced drift‐diffusion approach incorporating an electrochemical term to explain the short‐circuit, open circuit and fill factor losses that are experimentally measured after prolonged reverse bias is used. It is shown that holes can tunnel into the perovskite due to sharp band bending near the contact, accumulate within the bulk of the perovskite absorber, and trigger the oxidation of halides to form neutral halogens. The density of neutral halogens is much higher in reverse bias because there are hardly any electrons available to reduce the iodine. The resulting halogens act as bulk recombination centers. While the interstitial halogen density does decay when the cell is operated in forward bias, permanent degradation can occur if the iodine diffuses out of the perovskite layer. Finally, the ways in which changing parameters such as the mobile ion density or the series resistance at the contact can influence device performance and stability are discussed. Abstract : It is critical to understand how metal halide perovskite solar cells behave under reverse bias. Herein, it is shown that the power conversion efficiency losses after prolonged reverse bias are due to accumulation of holes within the bulk perovskite. Consequently, determinantal electrochemical oxidation reactions occur in the bulk, resulting in increased recombination and halide/halogen diffusion into charge transport layers.